Arrested Hydrocephalus in Childhood: Case Series and Review of the Literature - Hurni, Yannick; Poretti, Andrea; Schneider, Jacques; Guzman, Raphael; Ramelli, Gian Paolo (Neuropediatrics, 2018)
Introduction Hydrocephalus can be progressive or spontaneously arrested. In arrested hydrocephalus, the balance between production and absorption of the cerebrospinal fluid is restored. Patients are mostly asymptomatic, and no surgical treatment is necessary for them.Methods We performed a two-center consecutive case series study, aimed at investigating the safety of nonsurgical management of hydrocephalus in selected pediatric patients. We retrospectively selected all consecutive patients, suspected to suffer from arrested hydrocephalus and referred to our two institutions between January 2011 and December 2013. Data on clinical and radiological follow-up were collected until June 2017.Results Five children diagnosed with arrested hydrocephalus were included in the study. All patients presented macrocephaly as the main presenting sign. Associated mild-to-moderate stable motor disorders were assessed in four out of five cases. Typical symptoms and signs associated with acute raised intracranial pressure were absent in all patients. Magnetic resonance imaging studies showed ventriculomegaly in all patients. A diagnosis of arrested hydrocephalus was made in all five cases based on stable clinical and radiological findings during the initial observation. Conservative management based on active surveillance was, therefore, proposed. During the follow-up period, we observed stable or improved conditions in four out of five patients, while the remaining patient presented progressive hydrocephalus.Discussion Making a distinction between arrested and progressive hydrocephalus is fundamental, because of the opposed appropriate management. Any newly discovered case of hydrocephalus, not characterized by clear signs of progressive hydrocephalus, should benefit from active surveillance before any definitive decision is taken.
Keywords: hydrocephalus; arrested hydrocephalus; macrocephaly; childhood